Corneal Ulcer in a Southern Brown Howler Monkey (Alouatta guariba clamitans) - Treatment with Heterologous Serum - Cauduro da Rosa, Carolina; Anita Marchionatti Pigatto,; Guilherme Rech Cassanego,; Fabiano da Silva Flores,; Natália Karianne Brandenburg,; Gabriella De Nardin Peixoto,; Luis Felipe Dutra Corrêa, (Acta Scientiae Veterinariae, 2023)
Background: In the routine care of non-human primates, ocular trauma is frequent, however, unlike the small animal clinic, the prevalence of corneal ulcers is not documented. Among the numerous therapeutic options available in dogs, blood serum is being increasingly used as an adjuvant treatment in these conditions, due to its tear-like properties. Based on this, the present study aims to describe a case of corneal ulcer in a southern brown howler monkey (Alouatta guariba clamitans) attacked by a porcupine, and the use of heterologous serum obtained from an equine as an adjuvant treatment. Case: A southern brown howler monkey (Alouatta guariba clamitans), which had been attacked by porcupine quills, was treated at a University Veterinary Hospital. During the clinical examination, the presence of blepharospasm and secretion in the right eye was noticed. The ophthalmological examination, through the fluorescein test, detected the presence of an extensive superficial corneal ulcer in the right eye. After removing the spines, the corneal ulcer was treated with tobramycin-based eye drops, 1% atropine sulfate eye drops, and serum from equine blood in the form of eye drops, as an adjuvant therapy. After 5 days of treatment, the fluorescein test was repeated, which was negative in both eyes due to complete healing of the lesion, and thus the treatment was concluded. Discussion: The scarcity of scientific literature on wild animals is one of the factors responsible for the difficulty in advancing clinical and surgical procedures in non-human primates. Corneal ulcers are characterized by the loss of corneal epithelium with exposure of the stroma. The main clinical treatments adopted include antimicrobial therapy, analgesics, lubricating agents, and antiprotease drugs. Widely used as an adjuvant therapy in corneal ulcers in small animals, blood serum presents some advantages, as it is rich in growth factors, vitamins, immunoglobulins, and anti-collagenolytic substances, in addition to being obtained for a low cost. Considering the aforementioned, in the case reported, it was decided to use blood serum obtained from an equine as an adjuvant treatment of the corneal ulcer in a southern brown howler monkey. Complete healing of the corneal ulcer was confirmed in just five days, contributing to the well-being of this animal and contributing to the evolution of ophthalmology in this species that is still poorly studied. Keywords: corneal ulcer, southern brown howler monkey, heterologous serum. Título: Úlcera de córnea em bugio-ruivo (Alouatta guariba clamitans) - tratamento com soro heterólogo. Descritores: úlcera de córnea, bugio-ruivo, soro heterólogo.